Artificial Intelligence as a Catalyst for Green Economy and Sustainable Development - Lasih Amalia; Pudji Astuty (Cognitionis Civitatis et Politicae, 2024)
Artificial Intelligence (AI) has now become one of the key technologies in driving the transformation towards a green economy and sustainable development. AI offers innovative solutions in various sectors, such as energy, agriculture, transportation, and waste management, to increase efficiency, reduce carbon emissions, and optimize natural resources. This journal discusses how AI can be a catalyst in achieving the Sustainable Development Goals (SDGs) through a multidisciplinary approach. In the energy sector, AI facilitates the optimization of renewable energy use and the development of smart grids. In agriculture, AI helps create smart agricultural systems that minimize environmental impacts. In addition, the application of AI in waste management and the circular economy allows for optimal utilization of waste to reduce environmental pollution. However, there are several challenges that must be overcome, such as the digital divide, ethical and privacy issues, workforce disruption, and high implementation costs. This journal also provides several strategic recommendations, including collaboration between government, industry, and academia, strengthening policies, and investing in education and training to encourage inclusive and sustainable AI adoption. Based on the results of the research conducted, it can be concluded that the optimal application of AI can accelerate the transition to a green economy and strengthen the sustainable development agenda, but must be supported by appropriate regulations and active participation from all stakeholders.